Analisis Faktor-Faktor Yang Memengaruhi Keputusan Pembelian Secara Online Pada E-Commerce - Tri Rachmadhani, Sintya (Rifa'Institute, 2022)
Along with the rapid growth of the internet today, many products are emerging based on internet systems, one of which is e-commerce. The increasingly rapid growth of e-commerce has become a competitor to conventional stores which can now be seen from the decline in the number of mall visitors. The main point of this paper is to analyze the availability, price, promotion, service, trust, and variety seeking factors that influence online purchasing decisions at e-commerce. -commerce. The population and sample of this research are e-commerce users, by taking 100 samples using non-probability sampling technique and purposive sampling approach. The analysis technique used is multiple linear regression. The results of this study show that availability, price, promotion, service, variety seeking simultaneously have a significant effect on online purchasing decisions in e-commerce. Partially availability (availability) and search for variation (variety seeking) have a significant effect on online purchasing decisions in e-commerce, while price, promotion, service have an effect but not significantly on online purchasing decisions at e-commerce. Availability is the dominant factor influencing online purchasing decisions in e-commerce.